Embryo sac and microsporangium development in Pandanus (pandanaceae) - Cheah, C. H.; Stone, B. C. (Scientific Publishers, 1975)

(untitled)
Mega- and micro-sporogenesis in Pandanus parvus is described, with some ancillary observations from other species. The conclusions of Fagerlind (1940) are corroborated. The ovule is in contact with the atmosphere by means of the hair-lined stigmatic channel; it is anatropous and crassinucellate. The embryo sac is of monosporic origin and at maturity contains the usual 8 nuclei supplemented by supernumsrary and presumably diploid nucellar nuclei which 'migrate' into the sac from the nucellar tissue of the chalazal region. It is possible that they may contribute to the occurrence of parthenocarpy, and the vpossible occurrence of agamospermy. A hypostase is present. The development of the microsporangium is normal for angiosperms. The pollen grains are binucleate.